“Obtención de ajo (Allium sativum L.) en polvo y su evaluación en almacenamiento - Arce Arbildo,Lady (2006)
This work was carried out in the Agroindustrial Engineering Faculty Laboratories and the objectives were: to obtain the appropriate parameters for getting "Pink Valencian"powder garlic variety; to characterize the raw material and powder garlic and to evaluate its organoleptical characterize during the storage in two different kind of packing (Laminated and high - quality polyethylene). The sequence of the process for getting powder garlic was: selection, weigh, washing, chop, dry, refrigeration, grinding, sieve, bottle, seal and storage. The fresh garlic, with 4,96% of proteins and 61,65% of moisture content, was dried at 40 ºC, 50 ºC and 60°C; with 2mm, 3mm and 4mm of thickness; with dextrine (5% and 10%) and without dextrine and constant air velocity of 3 mis. lt was established through these experiments that the best conditions for the drying were: Temperature, 60°C, 2mm of thickness and without dextrine. During the first two months in storage showed that there were not significant differences in flavour and smell properties, but in the third month it was able to observe changes due to higher permeability of the high - quality polyethylene's, letting increase the moisture content from 4,7% to 9,5% dry base and compressing the product, but the laminated packing kept the initial humidity. The final results of the powder garlic tests were yield 33%, moisture content 4,7% dry base, crude proteins 16,69%, crude fat 0,69%, fibber 0,56%, carbohydrates 73,94%, ashes 3,42%; keeping the recommended State by the French Technical standard NF - V - 026 - 005.